Rocks and gems - Duhig, Holly; Kissock, Heather (Awesome infographics., 2021)
Provides an infographic overview about rocks with charts and fact boxes that inform how they are formed and describes the components of various types such as crystals and diamonds. Discusses famous ancient rock sculptures and the use of gemstones in jewelry. Concludes with a quiz and a glossary.